1984
DOI: 10.1136/jmg.21.5.364
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in the Freeman-Sheldon syndrome: two adults with probable autosomal recessive inheritance

Abstract: SUMMARY We report two sibs with the clinical features of the Freeman-Sheldon syndrome. The parents were unaffected and consanguineous, suggesting recessive inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
0
23
0
1
Order By: Relevance
“…Temtany and McKusick [9] observed that FSS affected two generations of three different families. However, there are also reports of the syndrome suggesting an autosomal recessive inheritance; in other words, of affected children born to parents who were clinically normal but possible carriers (heterozygotic) of the gene responsible for the syndrome [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Temtany and McKusick [9] observed that FSS affected two generations of three different families. However, there are also reports of the syndrome suggesting an autosomal recessive inheritance; in other words, of affected children born to parents who were clinically normal but possible carriers (heterozygotic) of the gene responsible for the syndrome [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1977; Kousseff et al, 1982;Fitzsimmons et al, 1984;Sanchez and Kaminker, 1986;Bonioli et al, 1987;Wang and Lin, 1987). Although the dominant form is fully established by several reports [McKusick, 1988, no.…”
Section: Introductionmentioning
confidence: 93%
“…In whistling face syndrome, feeding problems occur mainly due to microstomia [3][4][5]. Microstomia and tris mus are due to fibrosis and atrophy of the muscles about the mouth.…”
Section: Discussionmentioning
confidence: 99%